OUTPUT DAN MUTU PENDIDIKAN - Briliantina Indrati; Andi Hermawan (Institut Agama Islam Depok Al-Karimiyah Sawangan Depok, 2023)
Schooling is social institution needed to produce educational products and services, which useful for the existence of individual, community, or nation and state. In the term of economic of education, education production processes consume resources which scarce or limited, so education stakeholders should be capable to use the available resources effectively and efficiently. Educational results can be categories as consumption and investment. As consumption, the results are immediately and directly enjoyable, called outputs. While as investment, education give benefits indirectly and in the long term continuously, named outcomes. Also the results can be differentiating as economic valued outputs and non-economic valued outputs. The first one is outputs which potentially useful to get financial or monetary advantages, as knowledge and skills. While the second one is benefits which can not be measured as money, like friendship, happiness etc. The calculation of economical education results carried out by formulas: the earnings differentials, net present value, or internal rate of return, etc. This computation is very important to make decision or consideration in choose and continue study, to explain manpower condition, and to improve education program to meet with manpower demand.